Firm characteristics, distress risk, and average stock returns. Issue 2 (19th August 2014) - Simlai, Prodosh
Abstract : Purpose: In this paper we examine the empirical relationship between firm-level characteristics and the variability of the average portfolio returns of distressed firms. We evaluate the cross-sectional role of momentum in the market mispricing of distressed firms. We also disentangle distress risk associated with size and book-to-market ratio. Design/methodology/approach: We use all of NYSE, AMEX and NASDAQ stocks between January, 1972 and December, 2008, and study in detail the individual and joint role of firm characteristics. Using a measure of distressed stocks based on Campbell, Hilscher, and Szilagyi (CHS 2008), we provide new findings on how stock return anomalies are related to the interactions between firm characteristics and financial distress risk. Findings: Our findings show that the size and value effects are not due to distress risk. We also find that, contrary to the existing empirical evidence, momentum does not proxy for distress risk. Furthermore, in our cross-sectional analysis, momentum subsumes the effect of size risk, and book-to-market acts as an independent state variable. Research limitations/implications: The exposition of the paper is limited in many directions. To measure the extent of financial distress, we only use the model of CHS (2008). Since the level of distress is the key input in the paper, it would be interesting to use some other measure of distress, such as Z-score and O-score in our sample. Practical implications: Collectively, the pricing results in this paper help to foster a better understanding of the nature of distressed stocks, and the identification of distress risk premium. It will help scholars and investment professionals to make robust portfolio management decisions. Originality/value: Overall, this paper investigates an important research direction that can potentially shed new light on our understanding of the risk-return relationship of financially distressed stocks. We highlight the individual effect of momentum on the variability of the distressed firm's average returns. We present a formal cross-sectional test of the relationship between distress risk and firm characteristics that include momentum. None of them are quite known in the existing literature.